2020
DOI: 10.2147/dddt.s229063
|View full text |Cite
|
Sign up to set email alerts
|

<p>Bergenin Exerts Hepatoprotective Effects by Inhibiting the Release of Inflammatory Factors, Apoptosis and Autophagy via the PPAR-γ Pathway</p>

Abstract: These authors contributed equally to this workObjective: Hepatic ischemia reperfusion (IR) limits the development of liver transplantation technology. The aim of this study was to explore the protective effects of Bergenin on hepatic IR, particularly the elimination of reactive oxygen species (ROS) and activation of the peroxisome proliferators activated receptor γ (PPAR-γ) pathway. Methods: Initial experiments were performed to confirm the non-toxicity of Bergenin. Mice were randomly divided into sham, IR, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 54 publications
(58 reference statements)
3
31
0
1
Order By: Relevance
“…The treatment with bergenin effectively reduced the increased levels of TNF-α and IL-1β both in the sciatic nerve and in the spinal cord of neuropathic mice. These results agree with previous reports that bergenin diminishes the release of these cytokines under different inflammatory conditions [ 12 , 17 , 18 , 20 , 33 , 52 ]. Mechanistic hypotheses have been proposed to explain the roles of TNF-α and IL-1β in the pathophysiology of DN.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The treatment with bergenin effectively reduced the increased levels of TNF-α and IL-1β both in the sciatic nerve and in the spinal cord of neuropathic mice. These results agree with previous reports that bergenin diminishes the release of these cytokines under different inflammatory conditions [ 12 , 17 , 18 , 20 , 33 , 52 ]. Mechanistic hypotheses have been proposed to explain the roles of TNF-α and IL-1β in the pathophysiology of DN.…”
Section: Discussionsupporting
confidence: 93%
“…The surplus of electrons is then transferred to oxygen molecules, generating superoxide (O 2 - ), which in turn activates damaging pathways and gives rise to other ROS in a chain reaction [ 32 ]. Previous studies have shown that bergenin diminishes intracellular levels of superoxide and other ROS by increasing the activity of antioxidant enzymes, such as superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (Gpx) [ 12 , 16 , 25 , 26 ]. In this work, the antioxidant activity of bergenin was confirmed both in vitro, by the inhibition of NO production by J774 macrophages and in vivo, by the reduction of MDA and nitrite levels in neuropathic mice’s sciatic nerve and spinal cord.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two-day treatment of INS-1E cells with inflammatory cytokines reduced mitochondrial membrane potential, which was completely restored by the addition of beregnin with an EC 50 value of 2.27 μM ( Table 1 ). Generally, cellular ROS are in dynamic equilibrium, but increased ROS production due to inflammatory factors, may induce NF-κB, JAK/STAT, and MAPK pathways resulting in beta cell apoptosis [ 46 ]. Bergenin contains five hydoxyl groups, which play important role in its antioxidant activity.…”
Section: Discussionmentioning
confidence: 99%
“…This may be because autophagy-mediated lipid degradation provides energy for HSC activation, thereby promoting ECM formation and the progression of liver fibrosis. However, PPAR- γ activation has been linked to autophagy [ 13 , 14 ], but whether PPAR- γ plays an important role in the occurrence and development of liver fibrosis requires further investigation.…”
Section: Introductionmentioning
confidence: 99%